Design of a Neural Fuzzy Damper Vibration to Improve the Stability of Electric Power Systems - صندوق, عباس; ورقوزق, غيث; دبلو, معتز (Latakia University Journal -Engineering Sciences Series, 2021)
In this Paper a New Design Methodology for The Vibration Damper for Synchronous Machine Depends On Adaptive Neuro Fuzzy Inference System, Is Proposed in Order to Reduce the Oscillation Voltage in Electrical System and Find Out the Effectiveness of Proposed Damper in The Stability of the System, It Was Compared with Traditionally Power System Stabilizer. The New Damper Is Based On Adaptive Neuro Fuzzy Inference System Which Process the Signal of Rotation Speed of the Generator Then Control of the Excitation of Synchronous Machine, The Designed Damper Showed Ability to Reduce Amplitude Vibrations Arising from Failures and Thus Reduce the Time of Damping by Providing Additional Effort to Signal Entered to The Excitation System, compared with A Conventional Vibration Damper and Its Performance Is Better Than a Conventional Vibration Damper. The Proposed Design Offers a Good Possibility of Further Improving the Dynamic Stability and Thus the Stability of the Electrical System.